2010
DOI: 10.1021/jf903200h
|View full text |Cite
|
Sign up to set email alerts
|

Size Exclusion Chromatography for the Quantitative Profiling of the Enzyme-Catalyzed Hydrolysis of Xylo-oligosaccharides

Abstract: High-performance size exclusion chromatography (HPSEC) is a widely used method for the qualitative profiling of oligosaccharide mixtures, including, for example, enzymatic hydrolysates of plant biomass materials. A novel method employing HPSEC for the quantitative analytical profiling of the progress of enzymatic hydrolysis of different xylan substrates was developed. The method relies on dividing the HPSEC elution profiles into fixed time intervals and utilizing the linear refractive index response (area unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These elution behaviors are similar to those seen with high-performance size exclusion chromatography (HPSEC), which has been widely used for polysaccharide separation. Separation using HPSEC relies on a differentiation in the time of permeation of the polysaccharides into and out of the pores of the column, and this is related to the molecular size [42]. Vårum reported that when separating COS on a size exclusion column, the one with the highest DP eluted first [43].…”
Section: Resultsmentioning
confidence: 99%
“…These elution behaviors are similar to those seen with high-performance size exclusion chromatography (HPSEC), which has been widely used for polysaccharide separation. Separation using HPSEC relies on a differentiation in the time of permeation of the polysaccharides into and out of the pores of the column, and this is related to the molecular size [42]. Vårum reported that when separating COS on a size exclusion column, the one with the highest DP eluted first [43].…”
Section: Resultsmentioning
confidence: 99%
“…Poly/oligosaccharides are characterized by a combination of chemical and spectroscopic techniques. High‐performance size‐exclusion chromatography (SEC) is a popular approach for the qualitative profiling of OS mixtures (Rasmussen & Meyer, ). SEC has been demonstrated to be the most effective among a number of fractionation techniques to obtain prebiotic GaOS (Hernández, Ruiz‐Matute, Olano, Moreno, & Sanz, ).…”
Section: Analytical Methods To Evaluate Os and Microfloramentioning
confidence: 99%
“…100 mM sodium acetate (pH 6) with 0.02 % sodium azide was used as mobile phase and sample solution matrix and samples were separated on a Shodex SB-806 HQ GPC column 300x8mm) with a Shodex SB-Gguard column (50x6 mm) from Showa Denko K.K. (Tokyo, Japan) as described previously (Rasmussen and Meyer 2010). The precipitated material was dissolved to 5 mg/mL by vigorous shaking for 6 h at 60 °C, centrifuged (8000 g, 4 min) and filtered using a 0.22 μm syringe filter.…”
Section: High Performance Size Exclusion Chromatography (Hpsec)mentioning
confidence: 99%